Developing Rom (Realistic Outdoor Mathematics) Learning Model For Elementary School Students (International Journal of Scientific Research and Management (IJSRM), 2018)
The process of mathematics learning in Indonesia still face some problems, where some students still do not like even hate mathematics. This condition causes the passive and the low students’ learning achievement. The aim of this research was to describe the result of developing learning model which integrated Realistic Mathematics Education and Outdoor Mathematics, called ROM model using outdoor environment at elementary school. To develop the ROM model, it is employed steps which consist of stages, namely preliminary study, design, realization/construction, tests, and revisions. The test result found the ROM model and its instrumentations such as lesson plan, students worksheet, and achievement test was valid, practical and effective to be implemented for supporting teaching mathematics to improve activities and learning achievement of elementary school students.